A study of the awareness on occupational safety and health at the workplace in Kota Kinabalu Industrial Park (KKIP) / Mohd Zafiq Faisal Mohd Zaini and Abdul Hamid Jasni - Mohd Zaini, Mohd Zafiq Faisal; Jasni, Abdul Hamid (2014)
The Occupational Safety and Health practice at the workplace is very crucial to the organization especially in high risk sectors that need OSH to protect its workers. The research was applied in the area of Kota Kinabalu Industrial Park (KKIP) which focused in manufacturing sector. There are three variables that can influence the awareness of employees towards the occupational safety and health practices at workplace. Knowledgeable employees, role of employer, and workplace environment can enhance employees' awareness on Occupational Safety and Health practices at workplace. The main aim of the study is to determine the level of Awareness on Occupational Safety and Health practices at the workplace among selected manufacturers in KKIP. The study was using survey method by distributing questionnaires in selected manufacturers.